2014
DOI: 10.1073/pnas.1416707112
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of genome evolution that have accompanied host adaptation in Salmonella

Abstract: Many bacterial pathogens are specialized, infecting one or few hosts, and this is often associated with more acute disease presentation. Specific genomes show markers of this specialization, which often reflect a balance between gene acquisition and functional gene loss. Within Salmonella enterica subspecies enterica, a single lineage exists that includes human and animal pathogens adapted to cause infection in different hosts, including S. enterica serovar Enteritidis (multiple hosts), S. Gallinarum (birds), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
248
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 219 publications
(270 citation statements)
references
References 31 publications
21
248
0
1
Order By: Relevance
“…Comparison of the genomes of serovars belonging to the gastrointestinal pathovar with those belonging to the extraintestinal pathovar identifies genes important for intestinal survival, because they are undergoing decay in the latter group (43). That is, extraintestinal serovars accumulate mutations affecting genes important only for luminal growth, since no selective pressure exists to preserve their function; the result is pseudogene formation (43)(44)(45). Analysis of the nitrate reductases and their regulators found that only the narQP two-component system was rendered nonfunctional in extraintestinal serovars due to mutations (43).…”
Section: Discussionmentioning
confidence: 99%
“…Comparison of the genomes of serovars belonging to the gastrointestinal pathovar with those belonging to the extraintestinal pathovar identifies genes important for intestinal survival, because they are undergoing decay in the latter group (43). That is, extraintestinal serovars accumulate mutations affecting genes important only for luminal growth, since no selective pressure exists to preserve their function; the result is pseudogene formation (43)(44)(45). Analysis of the nitrate reductases and their regulators found that only the narQP two-component system was rendered nonfunctional in extraintestinal serovars due to mutations (43).…”
Section: Discussionmentioning
confidence: 99%
“…However, long-read sequencing is necessary to identify the exact composition and orientation of the prophages in these isolates. While there are no individual genes that are present uniquely in every clade A isolate, it is also possible that pseudogenes or SNPs may be related to adaptation to specific hosts or a systemic rather than gastrointestinal infection lifestyle as has been identified previously (30,62,63). The loss of diverse metabolic pathways that allow persistence in the gastrointestinal tract of the chicken during experimental infection is a feature common to the galliform-adapted Salmonella enterica subsp.…”
Section: Discussionmentioning
confidence: 99%
“…In Salmonella enterica, a widespread pathogen of mammals and birds, adaptation to hosts is thought to be multifactorial, with both gene gain and loss playing a part. 41,42 However, it is unclear whether these events are the cause or consequence of specialization. A recent gene-swapping study of V. fischeri strains hosted by Australian or Hawaiian Euprymna squids suggested that multifactor-mediated host specificity is not incompatible with single loci of large effect: there may in fact be multiple genes in a genome capable of greatly altering host affinity.…”
Section: Mechanisms For Maintaining Specificitymentioning
confidence: 99%
“…44,45 The horizontal acquisition of the permissive effector genes can lead to effective colonization of the same host plant by distantly related pathogen strains, thus breaking apart the phylogenetic hostmicrobe correlations typically associated with co-evolved symbioses. 44,45 Both horizontal gene transfer and genomic degradation probably play prominent roles in the evolution of specialization, 42,46 but to what extent remains an unresolved question. There is also the host perspective to consider, as interplay between host immunity and the microbiota constitutes an ongoing dialog between partners that often have competing evolutionary interests.…”
Section: Mechanisms For Maintaining Specificitymentioning
confidence: 99%